FGF-inducible 14-kDa protein (Fn14) is regulated via the RhoA/ROCK kinase pathway in cardiomyocytes and mediates nuclear factor-kappaB activation by TWEAK - Chorianopoulos, Emmanuel; Heger, Thomas; Lutz, Matthias; Frank, Derk; Bea, Florian; Katus, Hugo; Frey, Norbert (Basic research in cardiology, 2010)
Proinflammatory cytokines, including TNF family members, have been shown to play a critical role in cardiac remodeling. FGF-inducible 14-kDa protein (Fn14, TNFrsf12a or TWEAKR) is the smallest member of the TNF-receptor family. Currently, little is known about the functional role of Fn14 and its only known ligand TNF-like weak inducer of apoptosis (TWEAK) in the heart. We therefore evaluated the expression and regulation of Fn14 in cardiomyocytes and in experimental myocardial infarction. In order to study the regulation of Fn14, myocardial infarction was induced in CD-1 mice and neonatal rat cardiomyocytes were used for in vitro studies. TWEAK and Fn14 were markedly upregulated in the remodeling myocardium after experimental myocardial infarction in vivo. Likewise, fibroblast growth factor 1, norepinephrine and angiotensin II as well as mechanical stretch were able to strongly induce Fn14 expression in cardiomyocytes. This induction is mediated via the Rho/ROCK pathway, since the known inhibitors C3 exoenzyme for RhoA and Y27632 for ROCK prevented the upregulation of Fn14 in cardiomyocytes. Consistently, pretreatment of cardiomyocytes with siRNA against Rho A and ROCK also abolished Fn14 induction. Moreover, stimulation of cardiomyocytes with TWEAK promoted nuclear translocation of NF-kappaB and subsequent induction of NF-kappaB dependent genes such as RANTES and MCP-1. Conversely, when cells were pretreated with siRNA against Fn14, NF-kappaB activation by TWEAK was inhibited. We here provide the first evidence of a stress-induced regulation of the TWEAK/Fn14 axis in cardiomyocytes implying a role of the TWEAK/Fn14 pathway in cardiac remodeling.
Published online: 23 July 200
Gesehen am 14.03.2023